Rooster Cogburn - Wallis, Hal B., 1899-1986.; Millar, Stuart, 1929-2006.; Julien, Martin, 1924-2014.; Wayne, John, 1907-1979.; Hepburn, Katharine, 1907-2003.; Jordan, Richard, 1937-1993.; Zerbe, Anthony, 1936-; McIntire, John, 1907-1991.; Koslo, Paul, 1944-2019.; Romancito, Richard, 1953-; Lee, Tommy, 1900-1976.; Martin, Strother, 1919-1980.; et al. (Universal City, Calif. : MCA Universal Home Video, 1998)
A rough-edged deputy marshal teams up with a strait-laced missionary to track down a band of murdering bank robbers. During the pursuit of the outlaws, a warm rapport develops between the rough-and-tumble lawman and the flinty reverend's daughter.
Videodisc release of the 1975 motion picture.
"Suggested by the character 'Rooster Cogburn' from the novel 'True Grit' by Charles Portis."
Special features: Production notes ; cast and filmmakers' bios ; film highlights ; theatrical trailer ; scene access.
Director of photography, Harry Stradling, Jr. ; editor, Robert Swink ; music, Laurence Rosenthal.
John Wayne, Katharine Hepburn, Richard Jordan, Anthony Zerbe, John McIntire, Paul Koslo, Richard Romancito, Tommy Lee, Strother Martin.
Rated PG.
Keywords: Outlaws -- West (U.S.) -- Drama; Missionaries -- West (U.S.) -- Drama; Fugitives from justice -- Drama; West United States; DVD-Video discs; Video recordings for the hearing impaired; Drama; Feature films; Video recordings for the hearing impaired; Western films